2017
DOI: 10.1097/hcr.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Exercise Tolerance With Hemodynamic Parameters for Pulmonary Arterial Hypertension and for Chronic Thromboembolic Pulmonary Hypertension

Abstract: PH etiology should be considered when assessing exercise tolerance, whereas CPET can be effective in addition to hemodynamic assessment by means of RHC for periodic evaluation during followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(24 reference statements)
0
11
0
1
Order By: Relevance
“…6MWD and cardiopulmonary exercise test (CPET) were evaluated for exercise tolerance. 24 Pulmonary function was evaluated by measuring vital capacity as a percentage of predicted vital capacity (%VC), the ratio of forced expiratory through the femoral vein. A 6-Fr guiding catheter was engaged into the targeting sectional branches and a 0.014inch guide wire was crossed through the lesion.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…6MWD and cardiopulmonary exercise test (CPET) were evaluated for exercise tolerance. 24 Pulmonary function was evaluated by measuring vital capacity as a percentage of predicted vital capacity (%VC), the ratio of forced expiratory through the femoral vein. A 6-Fr guiding catheter was engaged into the targeting sectional branches and a 0.014inch guide wire was crossed through the lesion.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…Several papers have been recently published investigating the role of CPET in PH 5,6 and all of them showed a close relation between CPET and outcome. The principal findings of this study are substantially in line with abovecited reports, but we found a specific correlation among Ve/ VCO slope, DPG and pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Surie et al examined RV response to exercise with CMR in 13 CTEPH patients and 12 months after PEA; however, the patients exercised only at 40% of maximal workload . Other studies are retrospective, with the absence of simultaneous echocardiography or CMR imaging during exercise . Thus, our study adds new information by including consecutive CTEPH patients undergoing PEA, by using more advanced and newer echocardiographic modalities at rest and by studying the relationship between RV systolic function and physical capacity using maximal workload.…”
Section: Discussionmentioning
confidence: 98%